THE SOCRATIC METHOD AS A MEANS TO REMEMBER - Schusler Ralph Willard Jr. (TRANSMILLIY QO‘SHMA TA’LIM DASTURLARINING RIVOJLANISHI: O‘ZDJTU TAJRIBASI VA XALQARO SIFAT KAFOLATI TIZIMLARI BO‘YICHA ILMIY-AMALIY YONDASHUVLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This paper explores the challenge of employing the Socratic Method to help students answer questions posed in the classroom. Twenty-first-century distractions tend to impede this time-honored form of instruction. Cell phones have all but shown Socrates the door, as their lightening quick ability to unearth an answer makes pondering appear passé. This short-term solution, however, has long term effects on learning.